THE RESEARCH OF THE PROBLEM OF IDENTITY IN MODERN SCIENTIFIC SCHOOLS - Maratov Temur Gayrat ugli (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
This article discusses the formation of identity as a social phenomenon, its socio-psychological features. It also covers issues of fundamental research on the problem of identification.